(3SHd GdgOi hGdQTGO aj SjQI NjQ GdYHGOs - (3eMeO Hf jhSa GdOeTbj GdUGdMjs
(3ChdgG (B:s
(3LeGY CHhGH GdeZGRi GdJi ZRG ajgG QShd Gddg Udi Gddg Ydjg hSde GdHGH GdChd ai GdCPf HGdbJGd hfSN GdYah Yf GdeTQcjf hCgd GdcJGH s
(3BNQgG (B:s
(3jfJgi CKfGA HGH PcQ ESjPGf GdMLGL Hf YdGW QVi Gddg Yfg QShd Gddg Udi Gddg Ydjg hSde HYO aJM NHQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B978s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs